Human adipose-derived stem cells support lymphangiogenesis in vitro by secretion of lymphangiogenic factors - Ahmadzadeh, Nima; Robering, Jan Willem; Kengelbach-Weigand, Annika; Al-Abboodi, Majida; Beier, Justus; Horch, Raymund E.; Boos, Anja (Experimental Cell Research, 2020)
Lymphedema is a chronic progressive disease ultimately resulting in severe, disfiguring swelling and permanent changes of the affected tissues. Presently, there is no causal treatment approach of lymphedema. Therefore, most therapies are purely symptomatic. However, the recent use of stem cell-based therapies has offered new prospects for alternative treatment options. The present study was performed to investigate the effects of human adipose-derived stem cells (ADSCs) on human dermal lymphatic endothelial cells (HDLECs) in terms of basic in vitro lymphangiogenic assays (WST-8 assay, scratch assay, transmigration assay, sprouting assay, tube formation assay). The influence of ADSC-conditioned medium (ADSC-CM) on HDLECs was compared to recombinant VEGF-C, bFGF and HGF. Further ADSC-CM was characterized by protein microarray and enzyme-linked immunosorbent assay (ELISA). Although key-lymphangiogenic growth factors - like VEGF-C - could only be detected in low concentrations within the conditioned medium (CM), HDLECs were potently stimulated to proliferate, migrate and to form tube like structures by ADSC-CM. Despite concentrations more than hundredfold higher than those found in the conditioned medium, stimulation with recombinant VEGF-C, bFGF and HGF was still weaker compared to ADSC-CM. These results highlight the effectiveness of growth factors secreted by ADSC to stimulate HDLEC, potentially providing a promising new therapeutic approach for the treatment of lymphedema.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Adipose-derived stem cells (ADSCs); Cell therapy; Human dermal lymphatic endothelial cells (HDLECs); Lymphangiogenesis; Lymphedema; Secretome